1999
DOI: 10.1111/j.1467-842x.1999.tb01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing safe injecting rooms in Australia: attitudes of injecting drug users

Abstract: Objective: To investigate the attitudes of injecting drug users (IDUs) towards the establishment of safe injecting rooms (SIRs) in Melbourne, Australia. Methods: Multi‐site convenience sampling at Needle and Syringe Exchange Programs (NSEPs) within six Melbourne suburbs. Four hundred current IDUs were recruited directly through NSEP and participant snowballing. Respondents completed either a semi‐structured interview, anonymous self‐report questionnaire, face‐to‐face interview or participated in a focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 2 publications
4
22
0
Order By: Relevance
“…This was similar to another Australian study 4 which also found high rates of willingness to use such an injecting facility among injecting drug users in Victoria. A limitation to the interpretation of this high level of preference to use an MSIC in this study is that the respondents did not know what the nature of an MSIC in Kings Cross would be, since it had not yet been established.…”
Section: Discussionsupporting
confidence: 90%
“…This was similar to another Australian study 4 which also found high rates of willingness to use such an injecting facility among injecting drug users in Victoria. A limitation to the interpretation of this high level of preference to use an MSIC in this study is that the respondents did not know what the nature of an MSIC in Kings Cross would be, since it had not yet been established.…”
Section: Discussionsupporting
confidence: 90%
“…26 Our findings are also highly plausible since more than 500 IDUs visited the facility daily after it opened, and several feasibility studies have suggested that IDUs who inject in public would be the most likely to use safer injecting facilities. 13,27 Our observations suggest that the establishment of the safer injecting facility has resulted in measurable improvements in public order, which in turn may improve the liveability of communities and benefit tourism while reducing community concerns stemming from public drug use and discarded syringes.…”
Section: Discussionmentioning
confidence: 55%
“…As found in other SIF feasibility studies, this was conditional on MSIC being near the drug market, low threshold, hygienic, safe from police intervention, and offering assistance in case overdose. 38,39 This study was limited by the survey_s small sample size and day time only fieldwork; thus, the findings may not be representative of SG users, especially primary cocaine users and sex workers who primarily use in the evening. 40 There was, however, strong convergence between the findings of the survey and the key informant interviews, which allows for greater confidence in both data sets.…”
Section: Discussionmentioning
confidence: 99%